202 Predictors of Surgical Treatment and Postoperative Complications in the Pediatric Patient With Isolated Tethered Cord Syndrome. (1st August 2016) - Kashlan, Osama; Wilkinson, D. Andrew; Morgenstern, Hal; Maher, Cormac O.
Abstract: INTRODUCTION: Isolated tethered cord syndrome (iTCS) may be diagnosed in a symptomatic patient with a low-lying conus caused by a tight and/or fatty filum. Its incidence, patient characteristics, and outcomes after treatment with untethering surgery have been described largely through single-center studies. Indications for and the proper timing of surgery remain a subject of debate. METHODS: Utilizing the Optum Insight data set, we examined all pediatric patients in a large nationwide health care network with an International Classification of Diseases (ICD) diagnosis code of tethered cord between 2001 and 2014 (n = 3218). Using a combination of ICD and Current Procedural Terminology (CPT) codes, we identified iTCS diagnoses and untethering procedures. We examined demographic and clinical predictors of surgical intervention (n = 482) as well as postoperative complications. RESULTS: The incidence of iTCS in children over the entire study period was similar in females and males with incidence rates of diagnosis of 13 and 11 cases per 100 000 insured patient-years, respectively. Factors that increased the odds for surgical untethering included living in the West census region (unadjusted odds ratio [OR] 2.335 in comparison with tje New England census region, P < .001) and the presence of a syrinx (unadjusted OR, 2.189; P < .001). Of note, the presence of a Chiari malformation and sex did not affect the odds of undergoing surgery. In the surgical group, 3 to 6 year olds demonstrated the lowest odds of sustaining postsurgical complications (unadjusted OR, 0.297, when compared with patients younger than 1 year of age, P =.017). CONCLUSION: Analysis of a large nationwide health care network showed higher odds of untethering procedures for pediatric iTCS patients with a syrinx as well as significant regional variation. The 3- to 6-years age range was associated with lower surgical morbidity compared with older or younger patients.